2005
DOI: 10.1073/pnas.0406882102
|View full text |Cite
|
Sign up to set email alerts
|

The THAP domain of THAP1 is a large C2CH module with zinc-dependent sequence-specific DNA-binding activity

Abstract: We have recently described an evolutionarily conserved protein motif, designated the THAP domain, which defines a previously uncharacterized family of cellular factors (THAP proteins). The THAP domain exhibits similarities to the site-specific DNA-binding domain of Drosophila P element transposase, including a putative metal-coordinating C2CH signature (CX 2-4CX35-53CX2H). In this article, we report a comprehensive list of Ϸ100 distinct THAP proteins in model animal organisms, including human nuclear proapopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
193
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(205 citation statements)
references
References 34 publications
7
193
0
5
Order By: Relevance
“…We recently described an atypical zinc finger motif, characterized by a large C2CH module (Cys-X 2-4 -Cys-X 35-53 -Cys-X 2 -His) with a spacing of up to 53 amino acids between the zinc-coordinating C2 and CH residues (6). This motif, designated THAP domain or THAP zinc finger, defines a previously uncharacterized large family of cellular factors with more than 100 distinct members in the animal kingdom (6,7). We showed that the THAP domain of THAP1, the prototype of the THAP family (8), possesses zinc-dependent sequence-specific DNA binding activity and recognizes a consensus DNA target sequence of 11 nucleotides (THABS, for the THAP1 binding sequence) (7), considerably larger than the 3-4 nucleotides motif typically recognized by classical C2H2 zinc fingers (2,7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We recently described an atypical zinc finger motif, characterized by a large C2CH module (Cys-X 2-4 -Cys-X 35-53 -Cys-X 2 -His) with a spacing of up to 53 amino acids between the zinc-coordinating C2 and CH residues (6). This motif, designated THAP domain or THAP zinc finger, defines a previously uncharacterized large family of cellular factors with more than 100 distinct members in the animal kingdom (6,7). We showed that the THAP domain of THAP1, the prototype of the THAP family (8), possesses zinc-dependent sequence-specific DNA binding activity and recognizes a consensus DNA target sequence of 11 nucleotides (THABS, for the THAP1 binding sequence) (7), considerably larger than the 3-4 nucleotides motif typically recognized by classical C2H2 zinc fingers (2,7).…”
mentioning
confidence: 99%
“…These data provided the first links in mammals between THAP proteins, cell proliferation, and pRB/E2F cell cycle pathways and complemented genetic data previously obtained in model animal organisms. Indeed, in zebra fish and other fish species, the ortholog of cell cycle transcription factor E2F6, a repressor of E2F-dependent transcription during S phase (11) was found to contain a THAP zinc finger at its N terminus (7). In the nematode Caenorhabditis elegans, five distinct THAP zinc finger proteins (LIN-36, LIN-15B, LIN-15A, HIM-17, and GON-14) (7) were shown to interact genetically with LIN-35/ Rb, the sole C. elegans retinoblastoma homolog (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique may also require a priori selection of infusion sites, and as such it is also a biased approach. Unfortunately, some of the most common dystonia genes code for proteins that function in a variety of processes important for cell signaling, stability, and maintenance [48,[77][78][79][80]. In these cases, finding a compound that inhibits a specific function of the protein of interest is likely to be difficult or even impossible.…”
Section: Alternative Approaches For the Generation Of Rodent Models Omentioning
confidence: 99%
“…THAP4 consists of a N-terminal modified zinc finger domain, which has been proposed to bind DNA and of a C-terminus At-Nb-like domain, which could act as a NO sensor (32,113,114). It has been hypothesized that NO-binding to the C-terminal domain modulate the DNA binding activity of the N-terminal region, acting as an NO-dependent transcriptional regulator (31).…”
Section: Nitrobindinsmentioning
confidence: 99%